半乳凝素-3在非小细胞肺癌中的表达及相关性研究 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: Galectin-3 is involved in many physical and pathologic process, and is closely correlated with tumorigenesis, development and metastasis. The aim of this study is to investigate the gene expression and signifcance of Galectin-3 in normal lung tissue and non-small cell lung cancer (NSCLC) tissue. METHODS: Gene expression was examined using the immunohistochemical S-P method in 62 NSCLC cases and in 17 cases with normal lung tissue. RT-PCR verifed the expression of Galectin-3 at the transcriptional level. RESULTS: The expression rate of Galectin-3 in NSCLC tissue was 83.8% (52/62), which was signifcantly higher than that in normal lung tissue (P < 0.01). Galectin-3 expression was not correlated with sex (χ(2)=0.113, P > 0.05), age (χ(2)=0.220, P > 0.05), and histological type (χ(2)=0.012, P > 0.05), but was negatively correlated with pathological differentiation (r=-0.292, P < 0.05) and positively correlated with the clinical stage (r=0.336, P < 0.05) in NSCLC tissue. RT-PCR results showed that the expression level of Galectin-3 in NSCLC tissue was signifcantly higher than in normal lung tissue. CONCLUSION: Galectin-3 may be useful in lung cancer diagnosis and may increase diagnosis rate when combined with other lung cancer markers.